The role of nitrosative signaling in response to changing climates - Filippou, Panagiota S.; Fotopoulos, Vasileios; Antoniou, Chrystalla (My University, 2013)
The increased frequency and extent of global climatic changes and associated extreme environmental events remarkably influence plant growth and development, ultimately affecting crop productivity throughout the world. In addition to the well-documented enhanced accumulation of reactive oxygen species following abiotic stress factors, a large amount of research carried out during the last decade implicates the participation of nitric oxide and other reactive nitrogen species (RNS) leading to nitrosative stress in the plant’s responses to environmental stimuli. The imposition of abiotic stresses is known to cause overproduction of RNS, which ultimately inflicts a secondary oxidative and nitrosative stress, leading to various signaling responses. However, our understanding of nitrosative signaling remains poorly understood. The present chapter represents an up-to-date overview of the literature in terms of the important role played by nitrosative signaling in model as well as crop plants in response to increasingly changing climates.